The Traditional Malay House - Mohammad Affendy, Omardin
Traditional Malay house is a vital part of the Malay culture. The aesthetical design of the house bears strong influence of yesteryears’Islamic architecture. Additionally, considerations of residential prerequisites, cultural conformities and climate conditions do play important roles on drawing the blueprint. Elements surrounding its neighbourhood and the occupants’assessment of privacy are also taken into account. To the Malay, a house is more than just an abode – it is a conference hall, a mosque, a wedding ballroom, a labor room and a mortuary, all packaged into one.